The The Role of Prayer as Spiritual-Religious Coping in the Healing Process in the Perspective of Christian Psychology - Deak, Victor; Mengga, Ruth Caroline (IJOSMAS, 2023)
Prayer as a form of relationship that is built between a person and God is not only to express respect and express hatred but also as a medium used to raise supplications to God. Including asking for healing both when suffering from physical and psychological illness. So prayer becomes a spiritual coping mechanism that is spontaneously carried out when experiencing suffering, with the hope of getting relief and the hope of healing. Some psychologists fight spiritual coping mechanisms that are considered to make a person mentally weak because they depend on God and religion. Others recognize spiritual behavior including prayer as a part of the emotional coping mechanism. With reference to literature studies, researchers are looking for evidence of the significant role of prayer in the healing process. Prayer as a coping coupled with a consistent spiritual life is not only more effective but also an absolute thing to be able to feel the benefits. No prayer is effective without a good relationship with God.